Population specificity in the estimation of skeletal age and sex: case studies using a Western Australian population. (29th July 2019) - Franklin, Daniel; Flavel, Ambika
ABSTRACT: The expertise of the forensic anthropologist is grounded in the study of skeletal morphology relative to normal state; the latter is variously defined according to the complex interrelationship between biological function, genetics and intra-specific variation (amongst others). In relation to sex estimation, there are multiple dimorphic attributes in the adult skeleton that facilitate accurate sex estimations. It is, however, well established that there are population specific influences in not only skeletal growth, but also the expression and magnitude of sexual dimorphism (notwithstanding relative consistency in 'universally dimorphic traits' that relate to biological functioning – e.g., pelvic shape in relation to female functional requirements for childbirth). The recognition of the need for statistical quantification of forensic assessment is mandated by judicial requirement. Application of reference standards 'foreign' to that of the local jurisdiction, however, introduces an unknown variation and by association possible misclassifications. The present paper aims to empirically demonstrate the effect of the latter in a Western Australian population using multivariate classification statistics. We report here the analysis of a sample comprising three-dimensionally reconstructed cranial ( n = 400) and pelvic ( n = 400) multi-detector computed tomography (MDCT) thin-slice scans. In the morphometric analysis of cranial dimorphism, we demonstrate an unacceptably large sex bias; foreign standards thus frequently misclassify females.